Manajemen Kelembagaan pada MTs Al Washliyah Sei Kepayang dalam Meningkatkan Daya Saing - Istiqomah; Mesiono (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to explore the institutional management at MTs Al Washliyah Sei Kepayang in strengthening the school's competitiveness. The study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. Research informants consisted of the principal, vice principal, administrative staff, and teachers directly involved in the institution's management. The data obtained were analyzed using qualitative data analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. Data reduction was carried out by selecting and focusing information relevant to the research objectives, then the data was presented in the form of descriptive descriptions to facilitate interpretation. Furthermore, conclusions were drawn in stages based on findings obtained in the field. The results of the study indicate that institutional management at MTs Al Washliyah Sei Kepayang runs well through a clear organizational structure, the implementation of managerial functions, and the support of adequate human resources and infrastructure. Flagship programs and periodic evaluations also contribute to improving the quality of education and the institution's competitiveness, although there are still obstacles in the aspects of coordination and resource management that need to be improved.